Properties, Growth and Applications of Diamond - Nazare, M. H.; Neves, A. J. (Institution of Engineering & Technology Books International, Inc. [distributor], 2000)
Annotation Recent breakthroughs in the synthesis of diamond have led to increased availability at lower cost. This has spurred R & D into its characterization and application in machine tools, optical coatings, X-ray windows and light-emitting optoelectronic devices. This book draws together expertise from some 60 researchers in Europe and the USA working on bulk and thin film diamond. All fully refereed, the contributions are combined to form a highly structured volume with reviews, evaluations, tables and illustrative material, together with expert guidance to the literature.
Keywords: elektronické knihy; electronic books